Naprężenia, przemieszczenia i temperatura w ograniczonym ośrodku sprężystym przy uwzględnieniu sprzężenia termomechanicznego - Stefaniak, J. (Engineering Transactions, 1968)
The mass forces are disregarded in the present paper. By applying the method devised by W. Nowacki [1] partial separation of the equations of e equations of thermoelasticity is achieved by generalizing Galerkin’s function to the case of thermodynamical coupling Eqs. (1.13). A seminfinite body loaded by a concentrated harmonic force is considered as an example. The temperature, strain and displacement are obtained in the form of Hankel integrals. Expansion of the integrands in series of ε’δ, which is a small quantity, enables us to express the result in a simplified form. In the particular case of thermal insulation the results for the boundary plane are obtained in the form of elementary functions and modified Bessel functions of the first and second kind. The calculation of the integrals involved is carried out in the Appendix.